Toxoplasma gondii – Prevalence and Risk Factors in HIV-infected Patients from Songklanagarind Hospital, Southern Thailand - Chemoh, Waenurama; Sawangjaroen, Nongyao; Siripaitoon, Pisut; Andiappan, Hemah; Hortiwakul, Thanaporn; Sermwittayawong, Natthawan; Charoenmak, Bunsri; Nissapatorn, Veeranoot (Frontiers in Microbiology, 2015)
Toxoplasmosis is one of the most common opportunistic parasitic diseases in patients living with HIV/AIDS. This study aimed to determine the seroprevalence of Toxoplasma infection in HIV-infected patients and to identify associated risk factors in Toxoplasma seropositive patients. This study was conducted at a regional public hospital in Hat Yai, southern Thailand during October 2009 to June 2010. Blood samples were collected from 300 HIV-infected patients. Each subject also answered a socio-demographic and risk factors associated with Toxoplasma infection. The prevalence of anti-Toxoplasma IgG antibodies in HIV-infected patients was 109 (36.3%), of which 83 (76.2%) had past infection and 26 (23.9%) had recently acquired Toxoplasma infection as indicated by their IgG avidity. Multivariate analysis using logistic regression showed that gender difference (adjusted OR=1.69, 95% CI=1.05-2.72) was the only factor associated with Toxoplasma infection. From the results obtained, these HIV-infected patients could be at high risk of developing clinical evidence of severe toxoplasmosis. Therefore, it is necessary to introduce primary behavioral practices to prevent Toxoplasma infection among HIV-infected patients.